The Influence of Customer Perceived Restaurant Innovativeness (CPRI) of Meatball Restaurants on Brand Love and Brand Loyalty - Qorina Firkiana; Kurniawati Kurniawati; Yolanda Masnita (Universitas KH. Abdul Chalim Mojokerto, 2025)
The highly competitive landscape among food and beverage entrepreneurs in Indonesia compels brands to compete aggressively to attract and retain customers. Innovations in service are crucial to capturing consumer interest and maintaining their loyalty. Investigating whether innovations appeal to consumers in restaurants, particularly in the context of bakso (meatball), a local Indonesian dish, is thus imperative. This study aims to explore and analyze the influence of Customer Perceived Restaurant Innovativeness (CPRI) encompassing menu innovativeness, technology-based service innovativeness, experiential innovativeness, and promotional innovativeness on brand love and brand loyalty. A sample of 209 respondents, who have visited bakso establishments at least twice in the past three months, participated in the research. Respondents' responses underwent reliability and validity testing through Confirmatory Factor Analysis (CFA). Hypotheses were tested using Structural Equation Modeling (SEM) and Multi-group SEM with Mplus. Results indicate that the Stimulus-Organism-Response (S-O-R) theory contributes to enhancing both brand love and brand loyalty. The dimensions of CPRI technology-based service innovativeness, experiential innovativeness, and promotional innovativeness positively influence brand love and brand loyalty. This research is expected to assist managers in designing effective strategies to innovate within bakso restaurants and beyond.